Population Structure, Genetic Diversity, and Conservation Strategies of a Commercially Important Sleeper Fish, Odontobutis potamophilus (Gobiiformes: Odontobutidae) Based on Gene-Capture Data - Hu, Yun; Li, Hongjie; Xia, Jianhong; Li, Chenhong (Frontiers in Genetics, 2022)
Odontobutis potamophilus is a popular food fish in China, distributed mainly in the middle and lower reaches of the Yangtze River, where it is a famous delicacy and a newly focused species for aquaculture. The wild populations of O. potamophilus are facing the problem of overfishing and habitat degrading. Therefore, it is very necessary to investigate and protect the wild populations of O. potamophilus. In this study, 72 fish were sampled from 18 different sites over its distribution range. Nuclear sequence data of 4,267 loci were collected using a gene-capture method. Phylogenetic reconstruction revealed that there were three major clades: Oujiang clade (OJ), Qiantang and lower Yangtze clade (QY), and middle Yangtze clade (MY). The discriminant analysis of principal components (DAPC) and STRUCTURE analysis confirmed that there are three major groups within O. potamophilus. Fastsimcoal2 analysis corroborated the population history and suggested that there were discernible gene flow among these three groups, especially between QY and MY. Estimated pairwise FST suggested that Linhai (LH) and Shexian (SX) population were the most divergent pair (FST = 0.7077). Taking the nucleotide diversity, population divergence and admixture status all together in consideration, we recommend that the LH, Gaoyou (GY) and Chaohu (CH) populations could be protected as the preferred resource for breeding projects. According to the results of genetic analyses, all populations of O. potamophilus should be protected due to low genetic diversity.